Expressão imunoistoquímica e molecular da laminina-332 cadeia gama-2 em tumores mamários de cadelas - Zuccari, D. A.P.C.; Castro, R.; Jardim, B. V. [UNESP]; Mancini, U. M.; Polachini, G. M. (FapUNIFESP (SciELO), 2011)
Forty-eight cases of canine mammary cancer were investigated to evaluate the immunohistochemical distribution of the γ2 chain of laminin-332. Tumor cells were compared to a pool of normal mammary tissues using quantitative RT-PCR. The western blot was performed in eight tumor samples as complementary test to evaluate protein integrity. Immunohistochemistry experiments showed negative, focal, and weak expression of laminin-332 γ2 in tumors with the worst prognosis. Quantitative PCR revealed downregulation of the gene in 27 (56.2%) of the animals. Out of the 16 dogs with γ2 chain overexpression, seven were still alive. The western blot results showed bands generation of 36, 50, and 98kDa, suggesting degradation of laminin-332 γ2 in malignant tumors. The results suggest that, in the future, low expression and/or degradation of laminin-332 γ2 chain in canine mammary tumors may be used as an indicator of malignant potential. However, further studies are necessary to corroborate these results.
Immunohistochemical and molecular expression of laminin-332 gamma-2 chain in canine mammary tumors
Keywords: Adhesion molecule; Cancer; Dog; RT-PCR; Western blot